2016
DOI: 10.5815/ijmecs.2016.08.01
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Elementary Students' Programming Success based on Programming Environment

Abstract: Abstract-In the Republic of Croatia Informatics is an elective course in elementary school for students from 5th to 8th grade. When it comes to programming language teachers can choose between BASIC and Logo. There are a lot of new programming environments for learning and teaching programming like Scratch and also new ways of teaching programming like game based learning. This study compares attitudinal and learning outcomes of 7th-grade students programming in Logo and Scratch. The classes were normal classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The pre-test results applied to decide whether the groups were equal showed that more than half of the students in both the control and experimental groups left the majority of the questions blank since they did not experience the focused mathematics objectives before. Therefore, instead considering the pre-test results, students' previous year's mathematics course grade (ranges from 0 to 100) was adopted as the indicator of their current academic achievement as recommended in the literature (Bacon and Bean, 2006;Mladenovi c et al, 2016). Due to the test variable is normally distributed within groups, and other assumptions are appropriate, t-test was conducted.…”
Section: Participants and Research Designmentioning
confidence: 99%
“…The pre-test results applied to decide whether the groups were equal showed that more than half of the students in both the control and experimental groups left the majority of the questions blank since they did not experience the focused mathematics objectives before. Therefore, instead considering the pre-test results, students' previous year's mathematics course grade (ranges from 0 to 100) was adopted as the indicator of their current academic achievement as recommended in the literature (Bacon and Bean, 2006;Mladenovi c et al, 2016). Due to the test variable is normally distributed within groups, and other assumptions are appropriate, t-test was conducted.…”
Section: Participants and Research Designmentioning
confidence: 99%
“…Learning to program in higher education is difficult because it requires problem-solving and higher-order thinking skills [29][30][31]. e difficulty of expressing the solution in a language understood by the computer is a barrier for novice students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our previous research investigated the impact of using block-based and text-based programming languages and different programming contexts on programming success, motivation, and misconceptions [37][38][39][40][41]64]. Our other work will investigate the impact of using block-based programming languages as mediated transfer tools toward text-based programming languages on mastering basic programming concepts.…”
Section: Conclusion and Implications For Teaching And Future Researchmentioning
confidence: 99%